Ustrój i gospodarka samorządu terytorialnego w Hiszpanii z perspektywy 25 lat doświadczeń - Marczak, Jarosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
After enacting a democratic constitution in 1978, Spain started to construct a modern local government system. In 1981, statutes (constitutions) were passed for the newly established autonomous communities (regions), as well as the act regulating their sources of finance. Five years later Spain joined the European Union, which opened the possibility of accessing EU funds, mainly for the regions, and deriving huge benefits boosting the development of the then lagging country. It is, therefore, interesting to investigate if the country seized the opportunity? The article discusses the development path of local government and primarily of its key link - the autonomous communities - but also communes and provinces, with respect to the systemic, organizational, legal and economic solutions. Formulas implemented in Spain provide analytical material and constitute a source of inspiration. This is the main conclusion that can be drawn from the evolutionary process of changes, as well as the consistence and determination in pursuing the assumed goals, i.e. becoming one of the most developed countries. Especially interesting are the following characteristics of the Spanish local government system: distinct differences between the regional and lower levels of self-government (communes and provinces); financial stabilization of local governments - the rules of their financing are stable and predictable, hence they can pursue long-term strategies; centralized laws regulating the activities of local governments (the same laws are applied across Spain), unlike the autonomous communities that enjoy very broad autonomy; reduction of central government's transfers to autonomous communities in favour of their participation in the collected taxes and extensive formal institutions (commissions and councils) making up a platform for the co-operation between the State and autonomous communities, which is a very important solution. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 400-417